Tanggung Jawab Orang Tua Sebagai Wali dalam Pengurusan Harta Waris Anak di Bawah Umur Berdasarkan Hukum Islam - Muhammad Dzaky (CV Rewang Rencang, 2022)
The emergence of a Trust is caused by the breakup of the marriage either due to death or due to a court decision always bring legal consequences both against the husband or wife, children, and their property, especially against children who are underage. This paper will analyze how the authority of parents as guardians in the management of the inheritance of underage children based on Islamic law and decision-making regarding the authority and implementation of parents as guardians of heirs to inherited property. The author concludes that the Guardianship here is obliged to take care of itself and the property of the child under its guardianship and is obliged to provide religious guidance, education, and other skills.